CONVERSATION ANALYSIS BETWEEN SHAKIRA AND JIMMY FALLON “SHAKIRA’S MUSIC TEACHER WOULDN’T LET HER JOIN THE SCHOOL CHOIR” AT THE TONIGHT SHOW - Meilany, Anggara Dina; Nugroho, Raden Arief (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
Conversation analysis is a method for analyzing a conversation that involves two or morepeople. This analysis is required to determine what types of aspects are used during theconversation's occurrence. This research entitled “Conversation Analysis between Shakira andJimmy Fallon in the episode” Shakira’s Music Teacher Wouldn’t Let Her Join the SchoolChoir” is aimed to analyze and describes the aspects of conversation analysis used in the talkshow conversation. The researcher used qualitative descriptive as the analysis method based onthe theory of Paltridge. The data source were taken from Youtube video on The Tonight ShowStarring Jimmy Fallon Channel. This research resulted that there are five aspects of theconversation analysis applied such as opening, adjacency pairs, topic management, turn-taking,and feedback. The most dominant aspect of Conversation Analysis discovered in the talk showwas turn-taking aspect. Therefore, there were not closing, preference organization, and repair inthe talk show.